Realization and Extension of the Xfrog Approach for Plant Modelling in the Graph-Grammar Based Language XL - Henke, Michael; Kniemeyer, Ole; Kurth, Winfried (Computing and Informatics, 2017)
Two well-known approaches for modelling virtual vegetation are grammar-based methods (L-systems) and the Xfrog method, which is based on graph transformations expanding "multiplier" nodes. We show that both approaches can be unified in the framework of "relational growth grammars", a variant of parallel graph grammars. We demonstrate this possibility and the synergistic benefits of the combination of both methods at simple plant models which were processed using our open-source software GroIMP.